Comparison of Chest X-Ray and Lung Ultrasound for Diagnosing Community-Acquired Pneumonia in Children - Harivignesh, Harivignesh; Mogili, Hemanth (Journal of Neonatal Surgery, 2025)
Background: Community-acquired pneumonia (CAP) remains a leading cause of childhood morbidity. Chest X-ray (CXR) is the standard imaging modality but involves ionising radiation. Lung ultrasound (LUS) is a radiation-free alternative. This study compared the diagnostic accuracy of LUS versus CXR for paediatric CAP. Methods: A prospective study was conducted on 150 children (aged 6 months to 12 years) with suspected CAP between January and March 2025. All children underwent both CXR (interpreted by a paediatric pulmonologist) and LUS (interpreted by a paediatrician) within 4 hours of presentation. The reference standard was a clinical diagnosis confirmed by follow-up at 14 days. Sensitivity, specificity, and inter-observer agreement were calculated. Results: The prevalence of CAP was 72% (108/150). Lung ultrasound demonstrated sensitivity of 94.4% (95% CI: 88.1–97.9%) and specificity of 90.5% (95% CI: 77.9–97.4%) for diagnosing CAP. Chest X-ray showed sensitivity of 90.7% (95% CI: 83.4–95.5%) and specificity of 92.9% (95% CI: 80.5–98.5%). The difference in sensitivity was not statistically significant (p=0.21). Inter-observer agreement was substantial for LUS (κ=0.77) and almost perfect for CXR (κ=0.84). Ultrasound identified pleural effusions in 12 children (8%) that were missed on initial CXR. Conclusions: Lung ultrasound has comparable diagnostic accuracy to chest X-ray for paediatric community-acquired pneumonia and offers the advantages of no radiation, lower cost, and bedside availability. Lung ultrasound should be considered as the first-line imaging modality for suspected CAP in children.